Hubungan Pengetahuan dan Sikap dengan Partisipasi Suami dalam Perawatan Kehamilan Istri di Puskesmas Kampung Persatuan Tahun 2023 - Putri Handayani; Siska Suci Triana Ginting; Jenni; Safrina Loi (Nursing Applied Journal, 2024)
Background: Global data in 2017 showed that around 295,000 women died during and after pregnancy and childbirth. The vast majority of these deaths (94 percent) occurred in low-resource areas, and most were preventable. Sub-Saharan Africa alone accounted for around two-thirds (196,000) of maternal deaths, while South Asia accounted for almost one-fifth (58,000). four other sub-regions roughly halved their MMRs during this period: Central Asia, East Asia, Europe and North Africa. Overall, the maternal mortality ratio (MMR) in developing countries declined by just under 50 percent (WHO, 2020).Analytical research design with a cross-sectional approach. Cross-sectional is a research approach that emphasizes the time of measurement/observation of independent and dependent variable data only once at one time. This study was conducted to determine the relationship between one variable and another. (Notoatmodjo, 2018). Research Results Based on the results of data collection, the characteristics of respondents consisting of age, education, occupation and income are explained as follows. Respondents by age are mostly in the age range of 20-40 years as many as 40 people (63.2%), the rest are over 40 years old as many as 25 people (36.8%). Respondents have the most formal educational backgrounds completed, namely Senior High School (SMA) as many as 44 people (64.7%), and the least are college graduates as many as 3 people (4.4%), while Junior High School as many as 15 people (22.1%) and Elementary School as many as 6 people (8.8%). Most respondents work as farmers as many as 26 people (38.2%), the rest work as traders as many as 18 people (26.5%), employees as many as 16 people (23.5%), and others 8 as many as (11.8%). The most respondents earn per month above the UMK of Rp. 2.9 million as many as 36 people (52.9%), the rest are below the UMK of Rp. 2.9 million as many as 30 people (47.1%)  Research conclusion Based on the research results and discussion, the author concludes that there is a relationship between knowledge and husband's participation in wife's pregnancy care with a p value of 0.005 <0.05. There is a relationship between attitude and husband's participation in wife's pregnancy care.